AKTIVITAS ANTIPLASMODIUM EKSTRAK HIDROTROPI DAUN SAMBILOTO (Andrographis paniculata Ness.) SECARA In Vitro PADA Plasmodium falciparum STRAIN G-2300 RESISTEN KLOROQUIN - Yance Anas; Rita Dwi Ratnani; Laeli Kurniasari; Indah Hartati (Universitas Wahid Hasyim Semarang, 2020)
ABSTRACT The bitter leaf extract (Andrographis paniculata Ness.) has long been known as an anti-malarial. Our previous research has developed a bitter leaf hydrotrophy extract (BLHE) using a sodium acetate 2 mol/L as a hydrotop compound solution. The extraction process lasts for 2 hours, faster than conventional extraction. The result is two types of BLHE with different stirring temperatures, at 30°C (BLHE1) and 35°C (BLHE2). This study meant to determine and compare the in vitro antiplasmodial activity BLHE1 and BLHE2. The anti-plasmodial activity of BLHE1 and BLHE2 (0.1- 50.0) g/mL performed on a G-2300 strain of P. falciparum (chloroquine-resistant) after incubated for 48 hours (triplicate). The percentage of parasitemia determined through an examination of blood smears stained with Giemsa. The percentage of growth inhibition of P. falciparum evaluates by comparing percentage of growth with the control group and IC50 determine by probit analysis. The results showed that BLHE1 and BLHE2 respectively were able to inhibit the growth of P. falciparum of 14.62% - 43.25% (IC50: 59.689 μg/mL) and 24.06% - 49.48% (IC50: 44.541 μg/mL). Based on these data, BLHE should produce with sodium acetate 2 mol/L, with stirring at 35°C, because this condition will obtain BLHE that active as anti-plasmodial. Keywords: Anti-plasmodial, bitter leaf hydrotrophy extract, P. falciparum strain G-2300, in vitro